Upaya Meningkatkan Kemampuan Membaca untuk Referensi dalam Teks Bahasa Inggris Siswa Kelas VII-1 SMP Muhammadiyah Palangka Raya melalui Metode Inference: Effort to Improving Reading Ability for Reference in English at SMP Muhammadiyah Palangka Raya Students Class VII-1 through Inference Method - Waluyo, Tri (Anterior Jurnal, 2017)
This Classroom Action Research is backgrounded by the average of the students’ ability in English reading for refence of the 23 seventh grade students are low. Those are 7 (seven) in the range of 0-100. This study is aimed to know ; (1) the improvement of the SMP Muhammadiyah Palangka Raya seventh grade students ‘ ability in reading for reference during semester 2 in the academic year of 2015-2016, (2) the improvement of individual or classical achievement score averagelly in reading for refence, and (3) The improvement of the number of students reach the passing grade score. This study is applied the inference technique, and the steps are; Finding the contextual meaning to the words, which are infered, by translating into the Indonesian language, Then infering the meaning the words which are infered by changing the sentences contain the words into questions using “who or what”. After implementing 2 cycles, the findings of this study are; (1). The lowest improvement of individual achievement score in reading for reference averagely about 1.5 times or 150 % and the highest is 8.5 times or 850 %. Classically, the students’ ability in reading for reference is to be 5 times or 500 % improved, and (3) The total number of the students who reach the passing score grade is improved from 0 % to be 60.9 %. This shows that inference can increase the students in achieveing passing grade in reading for reference.